HUBUNGAN PENGGUNAAN LEARNING MANAGEMENT SYSTEM (LMS) PLATFORM CO-LEARN DENGAN KEMANDIRIAN BELAJAR SISWA KELAS XII DI SMA NEGERI 4 BANDUNG - Ranadya Szalsza Fachnurrulita, - (2022)
The implementation of online learning requires students to independently prepare their own learning, evaluate, control, and simultaneously maintain motivation in learning. To facilitate online learning, teachers use various methods, one of which is by using the Learning Management System (LMS) as a learning resource. Co-Learn platform is a platform that can guide students to increase their learning independence during online learning. This study aims to determine the relationship between the use of the Co-Learn platform on the learning independence of class XII students of SMA Negeri 4 Bandung. More specifically, this study aims to: is there a positive and significant relationship between the use of the Co-Learn Platform and learning independence. The sample used in this study was 40 people, which were determined by the Simple Random Sampling technique. The research method used is descriptive correlation method with a quantitative approach. The research instrument is a questionnaire type used to collect primary data, while data processing uses the calculation of the total score of each instrument, correlation analysis and significance test. The results of hypothesis testing at (α = 0.05) showed a correlation of 0.747 with a strong category so that H1 was accepted. In general, it can be concluded that there is a positive and significant relationship between the use of the Co-Learn platform and the learning independence of class XII students of SMA Negeri 4 Bandung.